2023
DOI: 10.3389/fpsyt.2023.1222972
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with suicide in physicians: a silent stigma and public health problem that has not been studied in depth

Narda Katherine Rátiva Hernández,
Tania Yaritza Carrero-Barragán,
Andrés Felipe Ardila
et al.

Abstract: Suicide is a complex and multifaceted public health issue that affects individuals from all walks of life, including healthcare professionals such as physicians. According to research, physicians have a higher risk of suicide compared to the general population, with an estimated suicide rate that is two to three times greater than that of the general population. Suicide in physicians can have devastating consequences, not only for the individual but also for their patients and colleagues. The factors contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…Our results show that, not being in a marital or akin to marriage relationship was more frequent in those with depression and/or anxiety. This finding is in line with previous research linking single marital status as a risk factor for negative health outcomes, including physician’s suicide ( Buckman et al, 2021 ; Rátiva Hernández et al, 2023 ). In the context of a culture of perfectionism and highly stressful endeavors, this finding seems to highlight the importance of meaningful human relationships for mental well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that, not being in a marital or akin to marriage relationship was more frequent in those with depression and/or anxiety. This finding is in line with previous research linking single marital status as a risk factor for negative health outcomes, including physician’s suicide ( Buckman et al, 2021 ; Rátiva Hernández et al, 2023 ). In the context of a culture of perfectionism and highly stressful endeavors, this finding seems to highlight the importance of meaningful human relationships for mental well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Married physicians had significantly less suicidal ideation than single physicians, a result that replicated previous studies [ 20 , 64 ]. A different result was reported by Gold et al [ 63 ], who reported increased deaths due to suicide among married physicians.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, increased working hours and night shifts were significantly associated with more depression in physicians but not with suicidal ideas. However, other studies reported that increased psychiatric disorders and suicidal ideation were associated with increasing working hours for physicians [ 40 , 64 , 65 ]. The wrong reporting or the smaller sample size may explain the difference in the present study.…”
Section: Discussionmentioning
confidence: 99%